Pengaruh Budaya Organisasi dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Penelitian dan Pengembangan Daerah Kota Palopo - Yustika Adelia; Mercy Paurin; Sadita Dandupa; Amri Amri; Marsal Marsal (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of organizational culture and work discipline on employee performance at the Regional Research and Development Agency (Balitbangda) of Palopo City. Employee performance is one of the key factors in an organization's success in achieving its goals, so it is important to understand the variables that influence it. Organizational culture is understood as the values, norms, and work habits that develop within the agency environment, while work discipline reflects employee compliance with established regulations, procedures, and work standards. This study uses a quantitative approach with an associative research design. The study population was all employees of Balitbangda Palopo City, with a sample of 33 respondents taken using a saturated sampling technique. Data collection was carried out by distributing questionnaires that had been tested for validity and reliability, and supported by secondary data from internal agency documents. Data analysis used multiple linear regression to test the partial and simultaneous effects of the two independent variables on employee performance. The results showed that organizational culture did not have a significant effect on employee performance. This indicates that although a work culture has been formed, its influence is not yet strong enough to encourage performance improvement. Conversely, work discipline has a significant and positive influence on employee performance, meaning that the higher the employee discipline, the more optimal the work results achieved. Simultaneously, organizational culture and work discipline continue to have a joint influence on employee performance, although only work discipline has been shown to make a significant contribution. These findings emphasize the importance of strengthening work discipline through supervision, imposing firm sanctions, and rewarding disciplined employees, while still building a more adaptive organizational culture and encouraging productivity.